Analisa Kehilangan Minyak (Oil Losses) Pada Proses Produksi Di Pt X - Arif Nurrahman; Edwin Permana; Azra Musdalifah (Jurnal Daur Lingkungan, 2021)
Palm oil is one of the crops that produce crude palm oil (CPO). Losses or loss of production is generally a natural thing in the palm oil processing process. Oil losses are the loss of the amount of oil that should be obtained from the results of a process but the oil cannot be obtained or is lost. The loss rate for palm oil is the amount of oil that is not taken up in the processing. The oil that is not taken is partly wasted into the boiler as fuel (oil from fiber). Oil losses are the loss of the amount of oil that should be obtained from the results of a process but the oil cannot be obtained or is lost. In testing oil losses using the socket extraction method. Soxlet extraction is a continuous extraction technique using a soxhlet, with the principle of distillation of solvent from the flask to the cooler, then dripping wet and immersing the sample located in the center of the soxlet apparatus.